From Crisis to Recovery: Optimizing Humanitarian Logistics for Long-Term Resilience in Cianjur - Aji, Barori Budi; Puja, Punang Amari; Qamari, Ika Nurul (Journal of Economics and Management Scienties, 2026)
The 2022 Cianjur Earthquake in West Java, Indonesia, registering a magnitude of 5.6, caused widespread damage and triggered 140 aftershocks, disrupting multiple sectors. This study investigates the humanitarian logistics management deployed in response to the disaster, focusing on the coordination and efficiency of aid distribution. Using a qualitative approach and comprehensive literature review, the research outlines how various stakeholders, including government agencies, local NGOs, and affected communities, collaborated to implement an effective logistics system. The findings highlight the importance of transparency, traceability, and inter-organizational coordination in ensuring timely and equitable aid delivery. Moreover, the study emphasizes that effective humanitarian logistics contribute not only to physical recovery but also to the psychological and social well-being of disaster survivors. This research contributes to the discourse on disaster management by offering insights into logistics strategies that support sustained recovery in post-disaster contexts.